ARIETAS BAHASA MASYARAKAT CINA DI SURABAYA (KAJIAN BAHASA ANTARETNIK) - Sartini, Ni Wayan (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 14 (2007): March 2007, 2007)
Abstrak Tujuan penelitian ini adalah untuk mengetahui varietas bahasa masyarakat Cina di Surabaya dan bahasa yang digunakan bila berkomunikasi dengan etnik setempat dan sesama suku. Metode yang digunakan adalah deskriptif kualitatif dengan mencari ciri-ciri linguistik yang khas pada masyarakat Cina di Surabaya. Penelitian ini menyimpulkan bahwa masyarakat Cina di Surabaya memiliki varietas bahasa yang unik seperti pencampuran antara bahasa Indonesia dan sufiks bahasa Jawa seperti sufiks ?e, mengubah kata-kata tertentu sesuai dengan dialek mereka seperti kata pergi menjadi pigi, menggunakan preposisi /dek/ atau /ndeq/ ?di?, tetap menggunakan sapaan-sapaan dalam bahasa Mandarin seperti tacik, koko, meme dan sebagainya. Masyarakat Cina bila berkomunikasi antarsuku cenderung menggunakan bahasa campuran antara bahasa Indonesia, Jawa, Mandarin, Hokkian. Namun bila berkomunikasi dengan masyarakat setempat atau antaretnik lebih memilih bahasa masyarakat setempat seperti bahasa Jawa dan bahasa Indonesia. Abstract The aim of this research, first is to recognize some linguistic features that has a role as a code marker of the language spoken by Chinese society in Surabaya. Secondly, to understand what language is spoken by Chinese family, among Chinese people or between Chinese and other ethnic groups. In theory, this research obtained some linguistic features at phonology level such as some changing sounds of /r/ becomes /l/, /t/ becomes /k/. Certainly not all sounds have such alternation. This can be identified from the age and the level generation of that Chinese society. At morphology level, the communication always been enriched by some Chinese greeting words. In the word formation, there are some word combinations between Indonesian and Javanese language, for instance the attachment of suffix ?e which similar to the suffix in Indonesia. Moreover, another special characteristic is the use of the prepotition dek / ndI? / ?at/ in?. The pronunciation alteration of a word can be seen in this example, the word pergi changes into pigi. In their daily communication with local society, the Chinese society in Surabaya apply language cmbination of Javanese and Indonesian. Among Chinese people in Surabaya, they speak some languages, namely Indoensian, Hokkian, Mandarin, Javanese, and the combination of those languages. A full- blooded Chinese always speak a language that consist of some Chinese elements or Mandarin. However, this depens on age and level generation.